Quantitative Evaluation of Performance during Robot-assisted Treatment - Peri, E.; Biffi, E.; Maghini, C.; Servodio Iammarrone, F.; Gagliardi, C.; Germiniasi, C.; Pedrocchi, A.; Turconi, A. C.; Reni, G. (Methods of Information in Medicine, 2016)
Introduction: This article is part of the Focus Theme of Methods of Information in Medicine on “Methodologies, Models and Algorithms for Patients Rehabilitation”. Objectives: The great potential of robots in extracting quantitative and meaningful data is not always exploited in clinical practice. The aim of the present work is to describe a simple parameter to assess the performance of subjects during upper limb robotic training exploiting data automatically recorded by the robot, with no additional effort for patients and clinicians. Methods: Fourteen children affected by cerebral palsy (CP) performed a training with Armeo®Spring. Each session was evaluated with P, a simple parameter that depends on the overall performance recorded, and median and interquartile values were computed to perform a group analysis. Results: Median (interquartile) values of P significantly increased from 0.27 (0.21) at T0 to 0.55 (0.27) at T1 . This improvement was functionally validated by a significant increase of the Melbourne Assessment of Unilateral Upper Limb Function. Conclusions: The parameter described here was able to show variations in performance over time and enabled a quantitative evaluation of motion abilities in a way that is reliable with respect to a well-known clinical scale.
Keywords: Assessment; robotics; rehabilitation; upper limb; cerebral palsy